THE INFLUENCE OF LEMB MUSCLE STRENGTH TRAINING ON LONG JUMP ABILITY IN SQUARE STYLE IN STUDENTS OF SMA NEGERI 1 KETAMBE CLASS XI ACADEMIC YEAR 2022/2023 - Fakhrur Rizal; Orbit Irwansyah; Melfa Br Nababan (Jurnal Penelitian Progresif, 2023)
The research is entitled "The effect of the exercise "Leg Muscle Strength on the ability to squat long jump in students at SMA Negeri 1 Ketambe Class XI for the 2022/2023 academic year". This research aims to reveal the effect of the exercise "Leg muscle strength on the ability to squat long jump in 124 students of SMA Negeri 1 Ketambe Class XI for the 2022/2023 academic year. The research sample was 35% of the total population of 24 students. The sampling technique was determined using the Random Sampling technique. This research is included in experimental research. The research design carried out was one group pretest-posttest design. For data collection, long jump measurements were used. Based on the results of data calculations and hypothesis testing as well as discussion of research results, the average value of long jump ability calculations before training "Leg muscle strength in students of SMA Negeri 1 Ketambe Class 10 meters. Based on the difference test analysis, the average difference obtained is 0.3 meters. Meanwhile, the calculated t is (1.76) and the t table is (1.71). It can be concluded that there is a significant influence between long jump ability after and before training "Leg muscle strength in students at SMA Negeri 1 Ketambe Class XI for the 2022/2023 academic year. This can be proven by comparing the t-count value which is greater than the t-table, (1.76>1.71).